2018
DOI: 10.3389/fpsyg.2018.01712
|View full text |Cite
|
Sign up to set email alerts
|

Games Used With Serious Purposes: A Systematic Review of Interventions in Patients With Cerebral Palsy

Abstract: The purpose of the present systematic review was to examine extant research regarding the role of games used seriously in interventions with individuals with cerebral palsy. Therefore, PubMed, PsyINFO, Web of Science, Scopus, and IEEE databases were used. Search terms included: “serious games” OR “online games” OR “video games” OR “videogame” OR “game based” OR “game” AND “intervention” AND “cerebral palsy.” After the full reading and quality assessment of the papers, 16 studies met the inclusion criteria. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
53
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(55 citation statements)
references
References 80 publications
2
53
0
Order By: Relevance
“…There are also several adjunctive interventions that when combined with task-specific motor training may augment the positive effects of training. These include electrical stimulation [65,[92][93][94], hydrotherapy [108,110,111], taping [159][160][161][162][163][164], transcranial direct current stimulation [101,[166][167][168], and virtual reality serious gaming [33][34][35][36][37][38][39][40][41][42][43][44][45][46][47] (yellow lights, weak positive). These interventions warrant more research as children reported finding gaming interventions rewarding and normalizing, and preferred electrical stimulation to wearing ankle-foot orthoses from a comfort perspective [93].…”
Section: Motor Interventionsmentioning
confidence: 99%
“…There are also several adjunctive interventions that when combined with task-specific motor training may augment the positive effects of training. These include electrical stimulation [65,[92][93][94], hydrotherapy [108,110,111], taping [159][160][161][162][163][164], transcranial direct current stimulation [101,[166][167][168], and virtual reality serious gaming [33][34][35][36][37][38][39][40][41][42][43][44][45][46][47] (yellow lights, weak positive). These interventions warrant more research as children reported finding gaming interventions rewarding and normalizing, and preferred electrical stimulation to wearing ankle-foot orthoses from a comfort perspective [93].…”
Section: Motor Interventionsmentioning
confidence: 99%
“…(See for example, the 16 studies retrieved from the systematic review of games used seriously in CP conducted by Lopes and colleagues. [21] Six of these efforts reported sample sizes in the single digits and only one reported on a cohort of more than 20 children.) There was also a disproportionate number of girls versus boys (7:1) who volunteered to participate in the pilot of PedBotHome.…”
Section: Limitationsmentioning
confidence: 99%
“…games used seriously) has likewise been shown to spur interest and motivate engagement fairly consistently across a wide range of therapeutic targets involving both lower and upper extremities. [21,22] Bringing these two strands of research together, robot-guided therapeutic maneuvers and games used seriously, has effectively created a new class of rehabilitative technology, which we will call assistive and/or rehabilitative (A/R) gamebots for ease of reference. The medical device payment structure in the US, for example, as yet has no classification under which A/R gamebots might be reimbursed in a child's therapy program.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Bedford et al [35] showed that there was a significant correlation between the age of first touchscreen use and the achievement of fine motor milestones and suggested that infants who actively use a touchscreen earlier also develop earlier manual dexterity abilities. In addition, interventions using interactive media such as video games have been shown to be effective in improving childhood movement disorders such as cerebral palsy [38] and developmental coordination disorder [39].…”
Section: Introductionmentioning
confidence: 99%